Modelling the influence of culture on Entrepreneurial competencies and business success of the women micro entrepreneurs in the informal sector of the economy - Nuraini Hashimu Salaudeen; Bello Garba Kofar Sauri (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2020)
The study examines the effect of culture on the relationship between the dimensions of Entrepreneurial competencies and business success of informal women micro-entrepreneurs in the northwest geopolitical zone of Nigeria. The study involves both descriptive and inferential statistics. With a random sample of 361 respondents, collected from a population of women micro-entrepreneurs, through the use of questionnaire, the obtained data were analyzed with a variance-based structural equation modelling, PLS-SEM. Findings revealed that opportunity, relationship, strategic, and organising competencies all have a positive and significant impact on business success of informal women micro-entrepreneurs in northwest Nigeria. Also, culture was found to moderate the relationship between relationship competencies and business success of women micro-entrepreneurs. These findings shows that any developmental programmes geared towards enhancing the performance of informal women micro-entrepreneurs in northwest Nigeria should focus on improving their entrepreneurial competencies, and the study practically illustrates the importance of interpersonal relations, such as, social interactions, and networking activities in the business success of informal women micro-entrepreneurs.